2001
DOI: 10.1054/bjoc.2001.1752
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of screening test (Hemoccult®) sensitivity in colorectal cancer mass screening

Abstract: Summary 3 controlled cohorts of mass-screening for colorectal cancer using a biennial faecal occult blood (HemoccultII ® ) test on well-defined European populations have demonstrated a 14% to 18% reduction in specific mortality. We aimed to estimate the sensitivity (S) of this HemoccultII ® test and and also mean sojourn time (MST) from French colorectal mass-screening programme data. 6 biennial screening rounds were performed from 1988 to 1998 in 45 603 individuals aged 45-74 years in Saône-et-Loire (Burgundy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…For example, in 1979 Jamieson [19] reported this bias in the analysis of the Stanford Heart Transplant data. This phenomenon has been frequently observed in the framework of cancer screening [18,20,21].…”
Section: Introductionmentioning
confidence: 64%
“…For example, in 1979 Jamieson [19] reported this bias in the analysis of the Stanford Heart Transplant data. This phenomenon has been frequently observed in the framework of cancer screening [18,20,21].…”
Section: Introductionmentioning
confidence: 64%
“…14,15 On the basis of the available literature, we estimated an average sojourn time for colorectal cancer of 3 years (range, 2 to 5). 13,16-18 …”
Section: Methodsmentioning
confidence: 99%
“…Randomised trials demonstrating FOBT screening effectiveness used a 3-day guaiac-based test (G-FOBT), a chemical test based on haemoglobin peroxidase-like activity whose accuracy is affected by dietary factors such as the presence of nonhuman haemoglobin and peroxidases in vegetables, or by certain drugs, particularly NSAIDs. Sensitivity of G-FOBT for CRC has been reported to be as low as 43-66%, based on a 2-year screening interval (Jensen et al, 1992;Launoy et al, 1997;Moss et al, 1999;Jouve et al, 2001); attempts to increase sensitivity either by rehydration (Church et al, 1997) or by increased reagent concentration (Petrelli et al, 1994;Allison et al, 1996) were associated with unacceptable loss in specificity. Several studies have suggested that immunochemical FOBT (I-FOBT) is more sensitive and specific than G-FOBT Saito et al, 2000;Zappa et al, 2001; Levi et al, 2006;Guittet et al, 2007), requiring no dietary restrictions, and might substantially improve screening cost effectiveness Saito et al, 2000).…”
mentioning
confidence: 99%